Quantitative assessment of a novel flow-through porous microarray for the rapid analysis of gene expression profiles - Wu, Ying (Oxford University Press, 2004)
A novel microarray system that utilizes a porous aluminum-oxide substrate and flow-through incubation has been developed for rapid molecular biological testing. To assess its utility in gene expression analysis, we determined hybridization kinetics, variability, sensitivity and dynamic range of the system using amplified RNA. To show the feasibility with complex biological RNA, we subjected Jurkat cells to heat-shock treatment and analyzed the transcriptional regulation of 23 genes. We found that trends (regulation or no change) acquired on this platform are in good agreement with data obtained from real-time quantitative PCR and Affymetrix GeneChips. Additionally, the system demonstrates a linear dynamic range of 3 orders of magnitude and at least 10-fold decreased hybridization time compared to conventional microarrays. The minimum amount of transcript that could be detected in 20 μl volume is 2–5 amol, which enables the detection of 1 in 300 000 copies of a transcript in 1 μg of amplified RNA. Hybridization and subsequent analysis are completed within 2 h. Replicate hybridizations on 24 identical arrays with two complex biological samples revealed a mean coefficient of variation of 11.6%. This study shows the potential of flow-through porous microarrays for the rapid analysis of gene expression profiles in clinical applications.